Effects of different concentration of dimethylsulfoxide and glycerol on motility, mortality and morphology of cryopreserved bull semen - Zainurin, Afiqah (2015)
Cryopreservation of gametes and embryos are routinely and widely applied in the mammalian. Cryopreserved sperm, oocytes and embryos are used for artificial insemination and embryo transfer in the livestock industry. Hence, the ability to predict post-thaw sperm quality and fertility from a routine sperm function assay would be greatly beneficial to the success of cryopreservation.The aim of this study was to evaluate the effects of different concentration of dimethylsulfoxide(DMSO) and glycerol on motility,mortality and morphology of cryopreserved bull semen. Semen samples from two bulls were collected twice from each bull and frozen in egg-yolk Tris extender with variable DMSO and glycerol concentrations of 5%,10% and 20%. The result was compare with control group which consist of 3% glycerol. Semen quality parameters assisted after thawing were sperm percentage progressive, percentage total motile, percentage live and percentage abnormal morphology of sperms. Results indicated that 5% glycerol had the highest effect on survivability of the sperm while 5% DMSO had lower survivability compared to the control group both for day 1 and day 7 post thawing. Other concentration shows decreasing in survivability as the concentrations increased. There is no significant different on mean percentage of abnormal morphology for both glycerol and DMSO (p>0.05). In conclusion 5% glycerol in egg-yolk Tris showed better survivability of cryopreserved bull semen.